2022
DOI: 10.1038/s41612-022-00240-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling historical changes in the hydrological cycle over land

Abstract: The sixth Intergovernmental Panel on Climate Change (IPCC) assessment report confirms that global warming drives widespread changes in the global terrestrial hydrological cycle, and that changes are regionally diverse. However, reported trends and changes in the hydrological cycle suffer from significant inconsistencies. This is associated with the lack of a rigorous observationally-based assessment of simultaneous trends in the different components of the hydrological cycle. Here, we reconcile these different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
2
10
0
Order By: Relevance
“…This might be an indication that approximately half of the observed response reflects increased plant transpiration in the region with the rest due to external climatic conditions, for example, regional warming and, hence, increased carrying capacity of the atmosphere with respect to the water vapor (Tian et al, 2022). This is consistent with the findings of Cui et al (2022): the trend of moisture convergence attributed to re‐greening, 0.26 mm/year 2 , is approximately half of the observed long‐term moisture convergence trend established by Hobeichi et al (2022; Table 3).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This might be an indication that approximately half of the observed response reflects increased plant transpiration in the region with the rest due to external climatic conditions, for example, regional warming and, hence, increased carrying capacity of the atmosphere with respect to the water vapor (Tian et al, 2022). This is consistent with the findings of Cui et al (2022): the trend of moisture convergence attributed to re‐greening, 0.26 mm/year 2 , is approximately half of the observed long‐term moisture convergence trend established by Hobeichi et al (2022; Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Comparing these figures with the results of Hobeichi et al (2022), who found global mean italicdP/italicdt=0.8 mm/year 2 , italicdE/italicdt=0.3 mm/year 2 and runoff italicdR/italicdt=0.6 mm/year 2 in 19802012 (Zhang et al (2016) obtained similar results), we conclude that a major part of precipitation and moisture convergence increase on land is likely due to re‐greening accompanied by increasing evapotranspiration—a pattern corresponding to case 3 in Figure 1b. This pattern, and not the reduction of moisture convergence with growing evapotranspiration (cases 1 and 2), appears to dominate the global response of the terrestrial water cycle to re‐greening (Table 3).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This interpretation of the importance of drying trends also appears to be supported by the patterns we see in the M2 time series, just at a different scale. In particular, the top contributing variables in the MC time series provide insights into the way macroclimatic change has potentially influenced seasonal trends while the most important variables in the M2 time series address various microclimatic and ecological functioning aspects of surface energy and hydrological dynamics (Table 6, Fig 6) [34,35,169,170]. The two most important variables in the M2 time series are surface wind speeds (SPEED), which appears to have been generally increasing across the south southwestern region of the study area over the past 40 years while remaining a consistently top model contributor, and bare soil evaporation energy flux (EVPSOIL), which is generally decreasing across the same area over this period while also remaining a top contributor across the time series.…”
Section: Discussionmentioning
confidence: 99%
“…These processes result in transporting the oceanic moisture towards the Indian subcontinent by advection processes, specifically, regulating water vapour over the land during monsoon season. The water vapour largely contributes to precipitation and consequently to the hydrological cycle of the climate system which is strongly coupled with major water reservoirs such as landmass, ice sheets and snow shields, and oceans (Hobeichi et al, 2022). The precipitation variability has widespread effects on water scarcity as water is an indispensable commodity for survival of which only $2.5% is available as freshwater (Gadgil, 2006;Kathayat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%